Setting Up the World Health Organization (WHO) Singapore Emergency Medical Team (SGEMT) for a Type 1 Fixed Facility Deployment - Li Juan Joy Quah; Shu Fang Ho; Doreen Tan; Fadhilah Ishami Muhammad Faisal; Kee Chong Ng (ASEAN Journal of Disaster Health Management (AJDHM), 2025)
Introduction: The World Health Organisation (WHO) Emergency Medical Team (EMT) initiative was formed in 2010 and is part of the United Nations’ (UN) international disaster management and response ecosystem. To date, WHO has verified more than 35 EMTs internationally. The Association of Southeast Asian Nations (ASEAN) Regional Capacity on Disaster Health Management (ARCH) project was established in 2016 and is the collaboration mechanism for comprehensive capacity strengthening on disaster health management within ASEAN. In 2018, ASEAN member states accepted WHO’s call for accredited EMTs and adoption of WHO standards. Within ASEAN, Thailand was the first to set up a WHO-EMT in 2019. In partnership with Singapore’s Ministry of Health (MOH), Singapore Health Services (SingHealth), the largest public healthcare cluster, was tasked to help set up Singapore’s in inaugural overseas emergency medical team under the WHO framework – the Singapore Emergency Medical Team (SGEMT) in 2023. Objective: This paper documents and shares key milestones during the creation of SGEMT. Methods: This is a qualitative study based on open-ended interviews with eight core members of the SGEMT planning committee and review of the relevant documents and processes pertaining to the overall disaster health response of the WHO EMT system and how SGEMT was developed by MOH and its public healthcare sector. A deductive approach to thematic analysis of the materials was performed. Results: Several themes were identified in the process of SGEMT formation. In chronological order, they were the whole-of-government approach, selecting the most suitable EMT typology, creating the EMT organizational structure, division of labour through creation of different working groups for different core technical standards and choosing the commercial tendering process for WASH and logistics. This process was augmented by guidance from WHO and regional partners through a mentorship programme. Conclusion: The process of creating SGEMT required strong political and organizational will. It was thematically sequenced into several crucial steps and required effective project management at various levels of labour division and invaluable input from WHO mentors. More academic papers should be written on the set-up of the WHO EMT, comparing experiences to obtain best practices and encouraging more teams to get accredited. This will greatly boost the international disaster response capabilities.